Mechanical properties of the magnetocaloric intermetallic LaFe11.2Si1.8 alloy at different length scales. (15th February 2019) - Glushko, Oleksandr; Funk, Alexander; Maier-Kiener, Verena; Kraker, Philipp; Krautz, Maria; Eckert, Jürgen; Waske, Anja
Abstract: In this work the global and local mechanical properties of the magnetocaloric intermetallic LaFe11.2 Si1.8 alloy are investigated by a combination of different testing and characterization techniques in order to shed light on the partly contradictory data in recent literature. Macroscale compression tests were performed to illuminate the global fracture behavior and evaluate it statistically. LaFe11.2 Si1.8 demonstrates a brittle behavior with fracture strains below 0.6% and widely distributed fracture stresses of 180–620 MPa leading to a Weibull modulus of m = 2 to 6. The local mechanical properties, such as hardness and Young's modulus, of the main and secondary phases are examined by nanoindentation and Vickers microhardness tests. An intrinsic strength of the main magnetocaloric phase of at least 2 GPa is estimated. The significantly lower values obtained by compression tests are attributed to the detrimental effect of pores, microcracks, and secondary phases. Microscopic examination of indentation-induced cracks reveals that ductile α-Fe precipitates act as crack arrestors whereas pre-existing cracks at La-rich precipitates provide numerous 'weak links' for the initiation of catastrophic fracture. The presented systematic study extends the understanding of the mechanical reliability of La(Fe, Si)13 alloys by revealing the correlations between the mechanical behavior of macroscopic multi-phase samples and the local mechanical properties of the single phases. Graphical abstract: Image 1